ANALISIS PENGARUH FIRM SIZE DAN DEBT TO EQUITY RATIO TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA TAHUN 2018-2021 DENGAN RETURN ON ASSET SEBAGAI INTERVENING - Lestari, Ayu Tri; Sari, Lita Permata; Pramitasari, Triska Dewi (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
Company value is significant for investors in determining stock investment because information on company value will help investors know which stocks have good value and are developing well. This study aimed to analyze the effect of Firm size and Debt to Equity Ratio oni Firm value with Return on Asset as an intervening variable. The population in this study are food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange for 2018-2021. The results of the direct effect hypothesis test using the Smart PLS 3.0 application show that Firm size has a negative but insignificant effect on Return on Asset, and Debt to Equity Ratio has a significant negative effect on Return on Asset. Firm size has a negative but insignificant effect on firm value, Debt to Equity has a positive but insignificant effect on firm value, and Return on Asset has a significant positive effect on firm value. The results of the indirect effect hypothesis test show that the Firm size and Debt to Equity Ratio variables on firm value through Return on Assets together have a negative but insignificant effect.